Docosahexaenoic acid-concentrated fish oil supplementation in subjects with mild cognitive impairment (MCI): a 12-month randomised, double-blind, placebo-controlled trial - Lee, Lai Kuan; Shahar, Suzana; Chin, Ai-Vyrn; Yusoff, Noor Aini Mohd (Psychopharmacology, 2013)
Rationale Epidemiological studies have suggested a beneficial effect of fish oil supplementation in halting the initial progression of Alzheimer’s disease. However, it remains unclear whether fish oil affects cognitive function in older people with mild cognitive impairment (MCI). Objectives This study investigated the effects of fish oil supplementation on cognitive function in elderly person with MCI. Methods This was a 12-month, randomised, double-blind, placebo-controlled study using fish oil supplementation with concentrated docosahexaenoic acid (DHA). Thirty six low-socioeconomic-status elderly subjects with MCI were randomly assigned to receive either concentrated DHA fish oil ( n = 18) or placebo ( n = 18) capsules. The changes of memory, psychomotor speed, executive function and attention, and visual-constructive skills were assessed using cognitive tests. Secondary outcomes were safety and tolerability of the DHA concentrate. Results The fish oil group showed significant improvement in short-term and working memory ( F = 9.890; ηp 2 = 0.254; p < 0.0001), immediate verbal memory ( F = 3.715; ηp 2 = 0.114; p < 0.05) and delayed recall capability ( F = 3.986; ηp 2 = 0.121; p < 0.05). The 12-month change in memory ( p < 0.01) was significantly better in the fish oil group. Fish oil consumption was well tolerated, and the side effects were minimal and self-limiting. Conclusions This study suggested the potential role of fish oil to improve memory function in MCI subjects. Studies with larger sample sizes, longer intervention periods, different fish oil dosages and genetic determinations should be investigated before definite recommendations can be made.